(untitled) (Fiep Bulletin - online, 2014)
This research had the goal to verify if the physical education teachers apply the dance discipline considering the different concepts presented on the pedagogical practice of physical education. The reports were made with 21 teachers graduated in Physical Education that are teaching on elementary school and that are using the dance discipline on their classes. A questionnaire was used as an instrument to collect data, it was applied by the authors of this article. According to the results, 100% of the teachers were aware about the pedagogical concepts of physical education and the majority were using the dance discipline based on the purposes of some of those concepts such as psicomotricity, culture and development. We could conclude that more studies are necessary on this area in order to provide a better application of the dance discipline as pedagogical knowledge on physical education.